2020
DOI: 10.1038/s41598-020-64355-z
|View full text |Cite
|
Sign up to set email alerts
|

Micro-Nano formulation of bile-gut delivery: rheological, stability and cell survival, basal and maximum respiration studies

Abstract: Probucol (PB) is a drug that exhibits significant hydrophobicity and substantial intra and inter individual variability in oral absorption, with a miniature bioavailability and complex three compartmental pharmacokinetic modelling due to its high lipid affinity, low stability and high octanol to water partition coefficient. Multiple attempts to formulate PB have not produced satisfactory stable matrices, drug-release profile or rheological flow properties for optimum manufacturing conditions, and with positive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 54 publications
4
26
0
Order By: Relevance
“…The post-stability drug content was similar to fresh microcapsules, which proved that there was no significant loss of PB under these testing conditions from both microcapsules. This study is consistent with a previous study where the F1 and F2 microcapsules' physicochemical compatibility was analysed [39]. Differential scanning calorimetry (DSC) results showed that PB did not participate in a cross-linking reaction with LVSA and BA, and did not compromise thermal and chemical integrity during the microencapsulation process, which is further supported by the Fourier-transform infrared spectroscopy (FTIR) analysis [39].…”
Section: Mechanical Strength Buoyancy Test and Drug Release Studiessupporting
confidence: 91%
See 3 more Smart Citations
“…The post-stability drug content was similar to fresh microcapsules, which proved that there was no significant loss of PB under these testing conditions from both microcapsules. This study is consistent with a previous study where the F1 and F2 microcapsules' physicochemical compatibility was analysed [39]. Differential scanning calorimetry (DSC) results showed that PB did not participate in a cross-linking reaction with LVSA and BA, and did not compromise thermal and chemical integrity during the microencapsulation process, which is further supported by the Fourier-transform infrared spectroscopy (FTIR) analysis [39].…”
Section: Mechanical Strength Buoyancy Test and Drug Release Studiessupporting
confidence: 91%
“…The reduction in IFN-γ and enhancement in IL-10 that the PB-ULCA microcapsules showed, are expected to decrease cell apoptosis and support cell function, which is supported by bioenergetics analysis [81]. Previously published data have displayed that the anti-oxidant activity of BAs enhanced β-cell viability [39,[81][82][83].…”
Section: Mechanical Strength Buoyancy Test and Drug Release Studiesmentioning
confidence: 73%
See 2 more Smart Citations
“…Previously, our studies have demonstrated that sodium alginate microcapsules significantly increase the brain uptake and associated neuroprotective effects of probucol-the highly lipophilic, antilipidemic drug [11]. Subsequent studies of ours confirmed that microencapsulation improves therapeutic efficiency of lipophilic drugs by protecting against degradation due to low stomach pH and efflux protein activity in the intestinal epithelium [12,13].…”
Section: Introductionsupporting
confidence: 55%